Study of Humanity as a Preventive Action Against Terrorism based on Behaviorism Theory - Nurhayati Mamun, Titin; Riyani, Tanty; Darjan, Murnisari (International Journal of Engineering and Technology, 2019)
Terrorism is becoming a serious issue, making the world such an unsafe place for humans. According to the European Convention on The Suppression of Terrorism in 1977, terrorism is no longer a criminal behavior against the state, but criminal behavior against humanity. The main cause of terrorism is the spread of radicalism, which semantically means: the notion of wanting change or social and political renewal by violent means. Of course, the eradication of radicalism and terrorism can only be done in a preventive way, namely through learning about the value of humanity from an early age. Based on the theory of Behaviorism, learning is the process of interaction between stimulus and response, so changes in behavior due to learning activities can be tangible. Hence the inclusion of humanitarian studies into the curriculum of education of each country is essential, because the value that is invested early on through the process of learning in the class will be more inherent in the minds of each student, the results and indicators of success can be easily measured. The implementation of the idea is adapted to the culture and educational conditions prevailing in each country, and we are in need of UNESCO involvement which is a Non-Government Organization under the United Nations to carry out the control function as an international organization engaged in education. The outcome of implementing this idea is certainly the decline in the number of radicalism-terrorism that takes place, making the world a more humanist place in the future.Â Â